Factors Determining Purchase Decision On Products Somethinc - Alifiya Ayu Firnanda; Wenti Krisnawati (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objective - The purpose of this research is to determine the influence of advertising attractiveness, influencer marketing, online customer reviews, and brand image on purchase decisions for Somethinc products. Design/Methodology/Approach - The research was conducted using a purposive sampling technique on 100 students at Muhammadiyah University of Gresik who were/had used, and had purchased at least once, Somethinc products. Then, the data was processed using IBM SPSS Statistics 24. Research Findings - It was found that Advertising Attractiveness, Influencer Marketing, Online Customer Reviews, and Brand Image had a positive influence on Purchase Decisions. Conclusions and Implications - The Somethinc product company can increase its Advertising Attractiveness, Influencer Marketing, Online Customer Reviews, and Brand Image to increase purchasing decisions, especially for the target market of Muhammadiyah University Gresik students.